An Exploratory Study On Scope Of Heuristic Methodology For Teaching In Hospitality Institutes During Pandemic ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2022)
Background: Learning is the on-going and continuous process through our lives , there are some learning which is done through exploring new ventures, thinking differently to solve a particular problem, some learnings are through experiments and demonstrations which cannot be taught in white and black, this is where the heuristics learning evolve and came into existence and it also help the teachers or educators to break the monotony of traditional teaching methods and let the student to swim in the ocean of knowledge and get to the shore with the best possible results to the problems. Objectives: This study is to find out the acceptability and enlist prominent attitude for the heuristic learning along with the major challenges faced by the faculty in implementation of same in hospitality education. Methodology: A descriptive cross –sectional design was adopted. The study was conducted in hospitality institutes pan India through online Google Forms in form  of questionnaire. Respondents were the faculty members of the institutes which were approached  by sending e-mails and through online survey. Total 210 respondents participated in survey. The  analysis was done by using relative importance of index along with averages and percentages.  Results: The most important attitude required by faculty for the implementation of heuristic methodology are the acceptance of unique solution of students (0.867) and after testing the solution  correct knowledge should be imparted to the students (0.856) (relative index of importance). The acceptability of heuristic methodology among the faculty is on average level with response of (39%) use of heuristic methodology for giving inputs to students. Various challenges in implementation are the syllabus needs a major change. The initial set of skills and knowledge are required by the  students (56%), completing the syllabus will be a challenge as all the topics in various subjects  are not teachable with heuristic methodology (38%). Conclusion: Respondents have given their responses towards mild acceptability towards using heuristic methodology, on the other hand the issues of challenges faced and various attitude required are strongly reflected towards the heuristic education. The need of proper training and right king of changes in syllabus are must of the successful implementation of this methodology.
Keywords: Heuristic Methodology; Learning; Explore; Discover; Facilitators